The Comparison of the Use of Black Turmeric (curcuma aeruginosa) and Combantrin as Worm Medicine at Sejati Drugstore In Makassar City - Zulfiah, Zulfiah; Saputra, Agung (Jurnal Farmasi Sandi Karsa, 2021)
One of diseases that always happen in developing country like Indonesia is worm disesase. Mostly this disease attract the children because the immune system is weak. This research has aim to know the use level of black turmeric (curcuma aeruginosa) and combantrin. This research used descriptive method. The researcher used research instrument with questionnaire that distributed into 80 respondents by using survey. The result of this research has shown that the highest level as anthelmintic between black turmeric and combantrin as much as 64% where the total percent showed the numbers of respondents used combantrin.